COMPARISON OF SELF-EVALUATED AND STUDENTS-REPORTED TEACHING EFFECTIVENESS OF MEDICAL TEACHERS: A CROSS SECTIONAL STUDY - Gul Shaikh; Seema Gul; Manya Tahir (Journal of University Medical & Dental College, 2020)
ABSTRACT BACKGROUND & OBJECTIVE: Opinions regarding student’s evaluation of faculty performance and use of formal feedback from students and/or lack of self-evaluation to improve their performance ranges widely. Keeping this under consideration, the present study was conducted to compare self-evaluated and students-reported teaching effectiveness of medical teachers. METHODOLOGY: A cross sectional study was conducted in Islamic international Medical college Rawalpindi, of three months duration (10th September to 10th December, 2018), on a sample of one hundred medical students and twenty medical teachers. Teaching effectiveness was assessed using “Self-assessment Instrument for Teacher Evaluation (SITE)” and students rated “Evaluation of teaching performance (CEID)” questionnaires. RESULTS: Teachers rated their teaching more effective with a mean score (M=111) than students (M= 109). The result was significant statistically. CONCLUSION: Self-evaluated teaching effectiveness was rated higher than students reported teaching effectiveness.